Tank-mix of chlorantraniliprole and manganese foliar fertilizers: Impact on rheological characteristics, deposit properties and cuticular penetration. (April 2018) - Zandonadi, César Henrique Souza; Burkhardt, Juergen; Hunsche, Mauricio; Cunha, João Paulo Arantes Rodrigues da
Abstract: The precise understanding of the interactions of adjuvants, agrochemicals and foliar fertilizers is essential to improve the efficacy of spray applications. In this study, we explored the influence of manganese foliar fertilizers (manganese sulfate and manganese nitrate) tank-mixed with an insecticide (chlorantraniliprole) and one organosilicone surfactant on the rheological properties of the solution, cuticular penetration and deposit characteristics on isolated tomato fruit cuticles. Higher Mn(NO3 )2 concentrations induced higher contact angles and surface tensions whereas higher MnSO4 concentrations induced only higher surface tension. The cuticular penetration (%) of MnSO4 and Mn(NO3 )2 were respectively 3% and 21% of the applied Mn amount. Addition of the organosilicone adjuvant significantly increased the cuticular penetration of both salts to 20% for MnSO4 and 35% for Mn(NO3 )2 . Both manganese salts, when mixed in equal proportion, showed a penetration of 25%, which was not statistically different if adjuvant was added (23%). The foliar fertilizers did not influence cuticular penetration of chlorantraniliprole. Our results confirm the fact that many processes cannot be predicted for field applications. Thus, these model systems can be used to try to understand, and in a few situations to try to predict what could happen, and understand the behaviour and causal relations only. Highlights: Deposit structures over the cuticle were influenced by organosilicon adjuvant. Tank mixture of agrochemichals did not change chlorantraniliprole penetration. A comparison was made of two manganese salts in tank mixture on rheological properties. Surface Tension of Manganese salts varied with their concentration.